PENGARUH MINAT KERJA TERHADAP KESIAPAN KERJA PADA PRAKTIK KERJA LAPANGAN SISWA PROGRAM DESAIN PEMODELAN DAN INFORMASI BANGUNAN SMKN 1 SUMEDANG - Ana Taryana, - (2019)
The research was conducted at SMKN 1 Sumedang, with the problems examined were lack of conformity in students work interests in the Modeling Design and Building Information (DPIB) program at SMK Negeri 1 Sumedang during the implementation of field work practices, which make students work readiness less than normal. In this study there are two variables namely Work Interest and Work Readiness in Field Work Practices (PKL). The purpose of this study was to describe the work interest of students, to find out the description of student work readiness, and to find out how much the influence of work interest on work readiness in the fieldwork practice of modeling design and building information students programs at SMKN 1 Sumedang. The study used a descriptive method with a quantitative approach and the data collection instruments on this form used questionnaires. The number of respondents in this study were 81nd respondents who were student of class XII modeling design and building information at SMKN 1 Sumedang. The data analysis technique on this form used simple regression analysis. The results of data processing indicate that the students work interest of the students is in the sufficient category and the work readiness on student fieldwork practices is also in the sufficient category. Based on the results of the regression test calculation, the results obtained that the interest in work has a positive and significant influence on work readiness in student student fieldwork pratices. This can be proven from the results of the calculation of the significance test where Fcount> Ftable with a value of 20,867> 3,962. The amount of influence can be seen from the results of simple regression calculations with the equation Y = 27,145 + 0,457 X. Therefore, work readiness in student fieldwork practices can be improved through adjusting students work interest.